2020
DOI: 10.1108/bij-11-2019-0505
|View full text |Cite
|
Sign up to set email alerts
|

AHP versus DEA: a comparative analysis for the gradual improvement of unsustainable suppliers

Abstract: PurposeData envelopment analysis (DEA) and analytical hierarchy process (AHP) are two widely applied methods to evaluate and rank suppliers in terms of sustainability. In this study, to investigate the extent to which potential differences in the outcomes of these two methods influence the benchmarking strategies, a comparative analysis based on a common set of data gathered from 19 logistics service providers is implemented. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The case for the proposed DEA model becomes strong in the view presented by Mahdiloo et al (2014), when supplier benchmarking becomes even more difficult when some of the inputs and output parameters become common. This is also supported by Rashidi (2020), where author has extensively compared AHP and DEA models in the context of supplier selection and concluded that DEA is suitable for firms that want to consider suppliers who can make significant performance improvements while making their businesses more sustainable. In case of e-commerce enterprises, it is a very difficult assignment to select the best set of suppliers that will contribute toward the overall profit of the firm.…”
Section: Methodsmentioning
confidence: 81%
“…The case for the proposed DEA model becomes strong in the view presented by Mahdiloo et al (2014), when supplier benchmarking becomes even more difficult when some of the inputs and output parameters become common. This is also supported by Rashidi (2020), where author has extensively compared AHP and DEA models in the context of supplier selection and concluded that DEA is suitable for firms that want to consider suppliers who can make significant performance improvements while making their businesses more sustainable. In case of e-commerce enterprises, it is a very difficult assignment to select the best set of suppliers that will contribute toward the overall profit of the firm.…”
Section: Methodsmentioning
confidence: 81%
“…This method is mainly applied when it is difficult to identify and compare direct relationships among multiple inputs and outputs and can be used to develop a more suitable decision-making model than AHP in environments with insufficient information. AHP Process chain companies and their performances have been compared to verify the practical effectiveness of each technique [34]. According to the findings, the AHP technique can provide detailed and gradual decision-making results through pairwise comparison in cases with large amounts of information, whereas the DEA method can provide effective decision-making strategies for situations with insufficient decision-making factors in a new environment.…”
Section: Data Envelopment Analysis (Dea) Methodsmentioning
confidence: 99%
“…Following the proposed analysis of eigenvalue and eigenvector used in a matrix calculation, ref. [29] describe a simple model, which is adapted for this research:…”
Section: Tvm and Sustainability Trade-off Analysismentioning
confidence: 99%
“…Refs. [29,55] provide details of the AHP model validation and the application of their mathematical models.…”
Section: Tvm and Sustainability Trade-off Analysismentioning
confidence: 99%
See 1 more Smart Citation